ll desiderio di essere governati. : Pastorato, neoliberalismo e produzione di colpa - Autieri, Mario (Nuovo Giornale di Filosofia della Religione (NGFR), 2021)
In the first part, dedicated to Foucault, we will rebuild the way in which a precise technique of individualization, the pastorate, turns itself into an individual's surveillance on itself in order that to support productive emotions. Benjamin focuses on the assimilation of capitalism to a religion that conceives itself not in relation to a moral interest, but as the priority practical interest that is expressed in an entirely immanent sphere. Pastorate Liberalism Guilty Capitalism Religion